Synergy Of Ecological Awareness And Blue Economy Implementation In Achieving Fisheries Sustainability In Indramayu - Rabbaniyah, Lathiefah; Riyantie, Mayang; Utari, Eka Dewi; Suhendry, Bayu; Kusumaningrum, Alifah; Negara, Dwi Ringga Edwid Dian; Lastuti, Yeti; Naufal, Hanif Afif (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study explores the synergy between ecological awareness and the implementation of blue economy principles in achieving fisheries sustainability in Indramayu Regency, Indonesia. The coastal area of Indramayu is known for its abundant fisheries resources but faces various threats such as overfishing, marine pollution, and coastal environmental degradation. Using a descriptive and correlational quantitative approach, this research analyzes the influence of two main variables, ecological awareness and blue economy implementation, on fisheries sustainability. Multiple linear regression was employed as it enables the simultaneous testing of more than one independent variable on a dependent variable. Data were collected from 45 active fishers in Karangsong Village, selected based on their direct involvement in fisheries activities. The regression results indicate that ecological awareness has a significant influence on fisheries sustainability (coefficient = 0.633; p < 0.01), followed by blue economy implementation (coefficient = 0.253; p < 0.01), with a simultaneous contribution of 66.1% to the variation in fisheries sustainability. The practical implications of this study highlight the need to enhance environmental education, strengthen the capacity of coastal communities, and optimize supporting infrastructure to ensure more equitable implementation of blue economy principles. These findings underscore that the success of sustainable fisheries strategies requires a combination of ecological awareness and community-based policy support.